Parents’ Perspectives on Quality ECCE Curriculum: Instrument Development - Shamsiah Sani, Siti; Taha, Hafsah; Md Taib, Rosfizah; Halim Masnan, Abdul; Nidzam Che Ahmad, Che; Yahaya, Asmayati; Baharom, Sadiah; Ramli, Saipolbahrin; Md Yassin, Sopia (International Journal of Engineering and Technology, 2018)
The aim of the study was to develop and validate the Early Childcare and Education (ECCE) Curriculum Instrument for Parents (QECCECI-P) by examining parents’ perspectives on the quality of the ECCE curriculum in the Malaysian context. The items were developed based on the existing literature that examines curriculum programmes for young learners. The instrument was validated by ECCE curriculum experts. More than 350 parents who send their children to government- or non-government-funded preschools were involved in the study. The study shows that two factors are related to parents’ perspectives on the quality of the ECCE curriculum: curriculum content and philosophy and core principles. The items in this instrument have factor loading values ranging from 0.479 to 0.84. The items also have high internal consistency with the alpha reliability coefficient values for each factor, which are more than 0.9. The results indicate that the instrument is valid and reliable for measuring parents’ perspectives on the quality of the ECCE curriculum in the Malaysian context.
Keywords: Curriculum; ECCE; Instrument Development.